2011
DOI: 10.1080/0031322x.2011.605845
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the conflict in Gaza on antisemitism in Belgium

Abstract: Taking Belgium as a case study, this article aims to assess the impact of a foreign conflict (the Israeli-Palestinian conflict in the Gaza Strip) on intergroup relations in Europe. It asks whether intensification of the conflict in Gaza increases the number of antisemitic incidents in Belgium, and makes use of a database of complaints to the Centrum voor gelijkheid van kansen en voor racismebestrijding (Center of Equal Opportunities and Opposition to Racism), a federal anti-racism agency, and of an analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…As such, the events itself were devastating and traumatic, appearing on front pages of newspapers around the world. Second, previous research such as Jacobs et al's study about the impact of Israeli military operations in Gaza on anti-Semitism in Belgium (Jacobs et al 2011) has shown that even distant events can influence group relations. Third, the Bali attack was at least partly targeted at European citizens-directly confronting Europe with the threat of Islamic terrorism.…”
Section: The Bali and Madrid Bombings And The Perception Of Immigrantsmentioning
confidence: 98%
See 1 more Smart Citation
“…As such, the events itself were devastating and traumatic, appearing on front pages of newspapers around the world. Second, previous research such as Jacobs et al's study about the impact of Israeli military operations in Gaza on anti-Semitism in Belgium (Jacobs et al 2011) has shown that even distant events can influence group relations. Third, the Bali attack was at least partly targeted at European citizens-directly confronting Europe with the threat of Islamic terrorism.…”
Section: The Bali and Madrid Bombings And The Perception Of Immigrantsmentioning
confidence: 98%
“…Other studies have focus on different events such as military interventions or ad campaigns. Using data on complaints filed in Belgium and a simple time-series design, Jacobs et al (2011) study whether the conflict in Gaza influenced anti-Semitism. Their results show that complaints about anti-Semitism increased during the Israeli military operation Cast Lead but abated several weeks after the operation.…”
Section: The Perception Of Immigrants and Terrorist Events: Theory And mentioning
confidence: 99%
“…The factors described should be understood against the background of the theoretical approach and context which have already been sketched. Following the Belgian sociologists Dirk Jacobs and colleagues, a distinction should be made between seeking an explanation for, on the one hand, the higher level of anti-Semitic and Islamophobic expressions in general since 2000 and, on the other hand, fluctuations in the registered expressions since then (Jacobs et al 2011). These fluctuations are strongly related to, as will be illustrated, outbursts of violence in the Middle East and acts of violence committed in the name of Islam in the West.…”
Section: Factorsmentioning
confidence: 99%
“…Hopkins (: 51) uses panel data to show ‘marked but shortlived effects of September 11’ on attitudes regarding migrants. In a similar vein, Jacobs et al (: 341) show that ‘complaints about antisemitism in Belgium indeed showed a statistically significant increase during the Israeli military operation Cast Lead … [but] this effect was not lasting and wore off after a couple of weeks’. Clearly, transient changes are of less social significance than long‐lasting ones.…”
Section: Introductionmentioning
confidence: 92%